Development of improved protocols for plant regeneration and genetic tranformation of rubber (Hevea brasiliensis Muell. Arg.) - Rahman, Md. Mahbubur (2014)
Hevea brasiliensis Muell. Arg. is the major source of commercial natural rubber which accounts for 99% of the world natural rubber production. The narrow genetic base, highly heterozygous nature, the long breeding cycle, low fruit set etc are the major limitations of crop improvement by conventional breeding of rubber tree. The recombinant DNA technology combined with tissue culture technique provides opportunity to introduced novel characters into commercially important crop plants, which cannot be achieved easily by conventional breeding. This study was undertaken to establish embryogenic callus culture and plant regeneration protocol via somatic embryogenesis from potential explants of H. brasiliensis (Clone RRIM 901) and evaluate the potential target tissues to design a genetic transformation protocol through Agrobacterium mediated transformation. In attempt to establish the embryogenic callus and somatic embryos of H. brasiliensis, the potential of zygotic embryo, leaf, cotyledon and root in forming embryogenic callus were examined in the basal MS (Murashige and Skoog) medium supplemented with different auxins and cytokinins at various concentrations. The highest callus formation frequency was observed from zygotic embryo explants, in MS medium containing 2.0 mg/L 2,4- D (90%) followed by NAA (50%), picloram (40%) and Dicamba (20%) after 8 weeks of culture. In response to embryogenic callus induction the highest 50% of the zygotic embryo explants produced embryogenic callus. A higher yield 70% of embryogenic callus was obtained when explants were cultured in MS medium containing 2.0 mg/L 2,4- D and 2.0 mg/L KIN (6-furfuralaminopurin) in presence of 0.5 mg/L NAA. Maximum embryos induction frequency (76.66%) were obtained on modified MS medium supplemented with 1.0 mg/L BAP (6- benzylaminopurine), and 2.0 mg/L GA3 (Gibberellic acid) in presence of 0.1 mg/L NAA after 4 weeks of culture. Frequency of embryo maturation was improved (70%) by inducing amino acid glutamin100 mg/L in the culture medium. Maximum plant conversion (80%) was observed on a medium supplemented with 0.3 mg/L GA3 and 0.2 mg/L IBA (Indole - 3- butyric acid). The in vitro micro-propagation capacity of somatic embryo derive plants in compare to mature grafted mother tree was evaluated. Maximum mean number of shoots (9.33 shoots / explant) formation were observed in MS medium supplemented with 2.0 mg/L BAP alone and 9.66 shoots / explant were produced in a combine effect of 2.0 mg/L BAP with 0.5 mg/L KIN after 8 weeks of culture. Root formation was observed only the shoot regenerated from the explant of somatic embryo derive plant. The plants were successfully acclimatized in natural conditions. A transformation protocol with LBA 4404 harbouring pCAMBIA1304 was established by evaluating the effect of different parameters on transformation efficiency by the expression of reporter gene gfp in rubber callus culture. The maintenance conditions for the embryogenic callus cultures, particularly a high auxin to cytokinin ratio (2.0 mg/L 2,4 D : 2.0 mg/L BAP : 0.5 mg/L NAA), the age of the culture and the use of a yellow green callus phenotype, were the most important factors for achieving efficient transformation. At the histological level, successful transient expression was related to the number of pro-embryogenic masses present in the embryogenic callus tissue. Transformed callus lines were selected and the stable expression of gfp gene detected without antibiotic pressure in rubber callus. In conclusion, the plant regeneration protocol via somatic embryogenesis developed using zygotic embryo explants of H. brasiliensis (Clone RRIM 901) has not been reported previously that could be applied to several rubber genotypes for production of large scale planting materials. The present regeneration system also used for developing transgenic callus lines by Agrobacterium- mediated gene transfer.